Instabilities in non-isothermal falling thin film flows - Jameel, Ahmed Tariq; Hamza, Mohammad Ameer; Hoda, Asif; Rahman, Tariq M.; Asrar, Waqar (Kulliyyah of Engineering International Islamic University Malaysia (IIUM) 50728 Kuala Lumpur Malaysia, 2017)
The stability and dynamics of thin liquid films subjected to van der Waals attraction, thermocapillarity and evaporative instabilities at the free surface, is studied using numerical simulations. For a Newtonian liquid, flow in thin liquid film on a solid support and bounded by a passive gas is represented by Navier-Stokes equation, equation of continuity and appropriate boundary conditions. The external effects are generally incorporated in the body force term of the Navier-Stokes equation. These governing equations can then be simplified using so called long-wave approximation to arrive at a nonlinear partial differential equation, henceforth called equation of evolution (EOE), which describes the time evolution of the interfacial instability caused by internal and/or external effects [1-3]. The comprehensive characterization of the nonlinear dynamics and surface morphology of thin-film requires efficient numerical method for the solution of the equation of evolution (EOE). Our thin-film flow configuration has been numerically simulated using a fully explicit finite difference formulation as well as an implicit finite difference scheme. The explicit finite difference scheme seems to replicate the solution from spectral method as well as implicit scheme to a high degree of conformity for most of the cases investigated. Thus explicit scheme presented here is a relatively simple numerical scheme with much less computational expense compared to Fourier spectral and implicit Crank Nicholson schemes for the full scale simulation of the various thin film models. However, the detailed numerical simulation of the thin film problem is being investigated.